Jan Hus in Czech Interwar Utopian Literature - Anna Amelina (Славянский мир в третьем тысячелетии, 2023)
The article deals with the role of Jan Hus in utopian constructions of the Czech interwar literature. During this period, a “wave of utopianism” was observed in the Czech Republic, it was utopia (both negative and positive) that became an extremely convenient means for understanding the complex of problems of the young Czechoslovak republic, and at that time the national element was preferred over the social one, which is also characteristic of the Slavic utopia in general. The overwhelming majority of the of utopian works at that time was written by the authors of the second and third-rate, but it is with them the national question comes to the fore, and the simpler and more primitive from an artistic point of view the texts of such authors were, the more clearly they express collective Czech national stereotypes. In such works, Jan Hus appears as a pillar of national culture. First of all, in terms of spirituality, as an inspirer for the construction of a peaceful and just life, where the Czechs finally find their place as a people, tarnished by suffering, and secondly, as an inspirer for military exploits. The greatness of his figure for the Czechs is so massive that it accelerates the utopian fantasies of Czech authors to world (at least cultural) hegemony or helps the world cope with its main enemy — the Germans. The article analyzes the following novels: “Telephone conversation of a Czech with an inhabitant of the planet Mars” (1918) by J. Mičan, “Death of Mankind” (1928) by J. Akana, “Red Vertigo” (1921) by A.M. Tichý, “Yellows against Whites” (1925) V. O. Lučan, “The Millennium of King Matthias” (1931) J. Černoch.